The singularity of the post-apartheid black condition - Ratele, Kopano (PINS-Psychology in Society, 2024)
Informed by Césaire’s awareness on the singularity of the black situation as well as Biko’s sense of the consequence of black-conscious solidarity for overcoming white racism, I present some notes concerning social cohesion. I counsel against social cohesion without socio-economic justice. I would like us to consider how we might radically rework what I see as the sentiment urging the discourse of social cohesion into socially-just solidarity in relation to the peculiarity of the black condition. I argue that even if social cohesion is considered a preeminent social ideal, it remains an empty signifier if not preceded by policies and programmes to overcome persisting socio-economic inequalities, especially because of the history and contemporary facts of colonial, apartheid and neo-apartheid injustices. I contend that projects intended to foster cohesion might do best if they are prefigured by a radical politics of socio-economic justice. In turn, a politics of social justice needs grounding in an understanding of our unique situatedness as a historically and currently unjust society.